2012
DOI: 10.1088/0004-637x/761/2/97
|View full text |Cite
|
Sign up to set email alerts
|

THE STAR FORMATION IN RADIO SURVEY: GBT 33 GHz OBSERVATIONS OF NEARBY GALAXY NUCLEI AND EXTRANUCLEAR STAR-FORMING REGIONS

Abstract: We present 33 GHz photometry of 103 galaxy nuclei and extranuclear star-forming complexes taken with the Green Bank Telescope (GBT) as part of the Star Formation in Radio Survey (SFRS). Among the sources without evidence for an AGN, and also having lower frequency radio data, we find a median thermal fraction at 33 GHz of ≈76% with a dispersion of ≈24%. For all sources resolved on scales 0.5 kpc, the thermal fraction is even larger, being 90%. This suggests that the rest-frame 33 GHz emission provides a sensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
200
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(221 citation statements)
references
References 92 publications
18
200
3
Order By: Relevance
“…We note that the coefficient here is 1.23 times larger than, but within the scatter of, the empirically derived relation between IR and radio free-free star formation rates (Murphy et al 2012). …”
Section: Data and Analysissupporting
confidence: 72%
“…We note that the coefficient here is 1.23 times larger than, but within the scatter of, the empirically derived relation between IR and radio free-free star formation rates (Murphy et al 2012). …”
Section: Data and Analysissupporting
confidence: 72%
“…Four of the galaxies in our sample were previously observed with the CCB by Murphy et al (2012), three of which were detected (M101 was reported as an upper limit by Murphy et al (2012) and is a 2.6σ marginal detection when the four sub-bands were averaged in our observations). Only one galaxy in our sample, Tol 35, was not detected when averaging the four sub-bands' fluxes.…”
Section: Fluxesmentioning
confidence: 66%
“…There is a well-established tight correlation between FIR and radio flux in star-forming galaxies (e.g., Helou et al 1985;Murphy et al 2006Murphy et al , 2012. When plotted on a log-log scale, the relationship between radio continuum and FIR flux for star-forming galaxies appears linear.…”
Section: Radio-far-infrared Correlationmentioning
confidence: 96%
See 1 more Smart Citation
“…These are lower than the estimate of 0.2 M yr −1 for the average SFR from analyses of stellar populations by Harris & Zaritsky (2009) and Rezaeikh et al (2014), but agree well with the recent star formation rate of 0.06 M yr −1 calculated by Whitney et al (2008) based on young stellar objects; these authors also give a range of SFR estimates of 0.05-0.25 M yr −1 from infrared and Hα data. However, all of these estimates correspond to an SFR over different timescales (e.g., Murphy et al 2012), as well as being subject to systematic effects; a more detailed study would be necessary to disentangle these effects. For the SMC, the amplitude at 10 GHz of 11 Jy from the Commander and LSF models gives an SFR of 1.1 × 10 −2 M yr −1 ; the LSF-CMB model gives a slightly higher value of 1.3 × 10 −2 M yr −1 from a flux density of 12.8 Jy.…”
Section: Lmc and Smcmentioning
confidence: 99%